Nutritional risk is a predictor for long-term mortality: 5-Year follow-up of the EFFORT trial. Issue 4 (April 2021) - Efthymiou, Andriana; Hersberger, Lara; Reber, Emilie; Schönenberger, Katja A.; Kägi-Braun, Nina; Tribolet, Pascal; Mueller, Beat; Schuetz, Philipp; Stanga, Zeno; ,; Fehr, Rebecca; Baechli, Valerie; et al.
Summary: Background and aims: The nutritional risk screening ( NRS 2002) is a validated screening tool for malnutrition. This study aims to investigate the prognostic value of the NRS 2002 and its individual components regarding long-term mortality and adverse outcomes in a well-characterized cohort of medical inpatients. Methods: We performed a 5-year follow-up investigation of patients included in the investigator-initiated, prospective, randomized controlled multicenter EFFORT trial that evaluated the effects of individualized nutritional intervention vs. standard hospital food. We used multivariable cox regression analyses adjusted for randomisation arm, study centre, comorbidities and main admission diagnosis to investigate associations between NRS 2002 total scores at time of hospital admission and several long-term outcomes. Results: We had confirmed mortality data over the mean follow-up time of 3.2 years in 1874 from the initial cohort of 2028 EFFORT patients. Mortality showed a step-wise increase in patients with NRS 3 (289/565 [51.2%]) and NRS 4 (355/717 [49.6%]) to 59.5% (353/593) in patient with NRS≥5 corresponding to an adjusted Hazard Ratio (HR) of 1.28 (95%CI 1.15 to 1.42, p ≤ 0.001) for mortality after one year and 1.13 (95%CI 1.05 to 1.23, p = 0.002) for the overall time period. All individual components of NRS including disease severity, food intake, weight loss and BMI provided prognostic information regarding long-term mortality risk. Conclusion: Nutritional risk mirrored by a NRS 2002 total score is a strong and independent predictor of long-term mortality and morbidity in polymorbid medical inpatients particularly in patients with high nutritional risk with an NRS ≥5 points.